Urbane Onomastik in Białystok. Zu Funktionen der Straßenbezeichnungen nach der NS-Umbennenung von 1942 - Feret, Andrzej S.; Feret, Magdalena Z. (Acta Neophilologica, 2021)
Street names not only have a topographical-spatial orientation function, but also reflect history and are a political and cultural tool. At the time of the National Socialist dictatorship, street and place names were changed in Germany. Also in the cities of then occupied Poland many streets and squares were renamed during the Second World War. The article aims to present the manner in which streets and squares in Białystok were named during World War II. An attempt is made to determine which functions can be observed in “new” urban designations.